2023
DOI: 10.3390/gels9020124
|View full text |Cite
|
Sign up to set email alerts
|

Xylan–Porphyrin Hydrogels as Light-Triggered Gram-Positive Antibacterial Agents

Abstract: In the present work, we report on the synthesis of light-triggered antibacterial hydrogels, based on xylan chains covalently bound to meso-tetra(4-carboxyphenyl)porphyrin (TCPP). Not only does TCPP act as a photosensitizer efficient against Gram-positive bacteria, but it also serves as a cross-linking gelator, enabling the simple and easy building of xylan conjugate hydrogels. The hydrogels were characterized by infrared spectroscopy (ATR-FTIR), scanning electron microscopy (SEM), along with swelling and rheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These materials are becoming important as a promising solution for wound management due to their tunability, softness, permeability, biocompatibility, or biodegradability. In the context of drug delivery, hydrogels benefit from their porosity, which enables drug encapsulation within a 3D polymeric network. Some antibacterial hydrogels have been particularly valuable in the context of light-induced therapies such as antimicrobial photodynamic therapy (aPDT). aPDT combines light, molecular oxygen, and a photosensitizer to generate reactive oxygen species (ROS) that oxidize lipids, proteins, DNA, and other biomolecules, leading to bacterial inactivation. Good transparency is, therefore, needed for hydrogels to perform well in aPDT, especially for wound dressing applications, and previous work has focused on optimizing their optical properties. , It was shown that electron-beam polymerized polyethylene glycol diacrylate (PEGDA) hydrogels have a higher transmittance over a broader wavelength range compared to their UV-cured counterparts, reaching values well above 90% …”
Section: Introductionmentioning
confidence: 99%
“…These materials are becoming important as a promising solution for wound management due to their tunability, softness, permeability, biocompatibility, or biodegradability. In the context of drug delivery, hydrogels benefit from their porosity, which enables drug encapsulation within a 3D polymeric network. Some antibacterial hydrogels have been particularly valuable in the context of light-induced therapies such as antimicrobial photodynamic therapy (aPDT). aPDT combines light, molecular oxygen, and a photosensitizer to generate reactive oxygen species (ROS) that oxidize lipids, proteins, DNA, and other biomolecules, leading to bacterial inactivation. Good transparency is, therefore, needed for hydrogels to perform well in aPDT, especially for wound dressing applications, and previous work has focused on optimizing their optical properties. , It was shown that electron-beam polymerized polyethylene glycol diacrylate (PEGDA) hydrogels have a higher transmittance over a broader wavelength range compared to their UV-cured counterparts, reaching values well above 90% …”
Section: Introductionmentioning
confidence: 99%